Risk Factors, Subsequent Disease Onset, and Prognostic Impact of Myocardial Infarction and Atrial Fibrillation - Stephan Camen; Dora Csengeri; Bastiaan Geelhoed; Teemu Niiranen; Francesco Gianfagna; Julie K. Vishram‐Nielsen; Simona Costanzo; Stefan Söderberg; Erkki Vartiainen; Christin S. Börschel; Maria Benedetta Donati; Maja‐Lisa Løchen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Although myocardial infarction (MI) and atrial fibrillation (AF) are frequent comorbidities and share common cardiovascular risk factors, the direction and strength of the association of the risk factors with disease onset, subsequent disease incidence, and mortality are not completely understood. Methods and Results In pooled multivariable Cox regression analyses, we examined temporal relations of disease onset and identified predictors of MI, AF, and all‐cause mortality in 108 363 individuals (median age, 46.0 years; 48.2% men) free of MI and AF at baseline from 6 European population‐based cohorts. During a maximum follow‐up of 10.0 years, 3558 (3.3%) individuals were diagnosed exclusively with MI, 1922 (1.8%) with AF but no MI, and 491 (0.5%) individuals developed both MI and AF. Association of sex, systolic blood pressure, antihypertensive treatment, and diabetes appeared to be stronger with incident MI than with AF, whereas increasing age and body mass index showed a higher risk for incident AF. Total cholesterol and daily smoking were significantly related to incident MI but not AF. Combined population attributable fraction of cardiovascular risk factors was >70% for incident MI, whereas it was only 27% for AF. Subsequent MI after AF (hazard ratio [HR], 1.68; 95% CI, 1.03–2.74) and subsequent AF after MI (HR, 1.75; 95% CI, 1.31–2.34) both significantly increased overall mortality risk. Conclusions We observed different associations of cardiovascular risk factors with both diseases indicating distinct pathophysiological pathways. Subsequent diagnoses of MI and AF significantly increased mortality risk.